Performance of Tomato (Solanum lycopersicum L.) Hybrids for Yield and its Contributing Traits under Mid-hill Conditions of Himachal Pradesh - Raj, Tanvi; Bhardwaj, Madan Lal; Pal, Saheb; Kumari, Santosh; Dogra, Rajesh Kumar (International Journal of Bio-resource and Stress Management, 2018)
With an objective to estimate the performance of tomato hybrids with respect to their yield and yield contributing traits, an experiment was conducted at the experimental farm of RHR&TS, Jachh, Kangra, Himachal Pradesh with 20 hybrids along with their 12 diverse parents and standard check Naveen 2000+, which is a leading commercial tomato hybrid in Himachal Pradesh. The hybrids were produced during Rabi 2015 by following line×tester mating design and were evaluated during kharif, 2016. The later experiment was designed in Randomized Complete Block Design (RCBD) with three replications. The obtained results revealed that the hybrid, EC-620410×Solan Lalima was earliest among all the entries in terms of days to 50% flowering, while both the hybrids between EC-8910155 and FT-5 were earliest in terms of days taken to marketable maturity. The hybrid between BT-1-1×FT-5 had maximum number of fruits cluster1 as well as maximum yield plant1. For average fruit weight, the hybrids of BT-1-1×Solan Lalima were found best among all the hybrids and their parents. The hybrid, LE-79-5×FT-5 produced maximum number of marketable fruits plant1. Moreover this hybrid recorded minimum severity of Alternaria blight (early blight). Hence, for commercial exploitation of heterosis for earliness and yield in tomato, these hybrids are needed to be tested in multiple locations for stability before releasing as varieties.